Renewable Energy and Negative Externalities: The Effect of Wind Turbines on House Prices - Martijn I. Dröes; Hans R.A. Koster (Tinbergen Institute, 2014)
In many countries, wind turbines are constructed as part of a strategy to reduce dependence on fossil fuels. In this paper, we measure the external effect of wind turbines on the transaction prices of nearby houses. A unique house price dataset covering the period 1985-2011 is used, including the exact location of all wind turbines built in the Netherlands. We find that house prices within a two kilometer radius of a turbine, after it has been constructed, decrease by about 1.4 to 2.3 percent on average. We find anticipation effects up to three years in advance of the construction of a wind turbine. We provide further evidence that the external costs of a wind turbine are at least 10 percent of its construction cost.
Keywords: R31; Q42; Q15; L94; 330; renewable energy; wind turbines; externalities; house prices